1978
DOI: 10.1104/pp.62.5.727
|View full text |Cite
|
Sign up to set email alerts
|

Lead Toxicity and Phosphate Deficiency in Chlamydomonas

Abstract: The addition of lead salts to phosphate-containing Chiamydomonas rei.harddi media caused precipitation of Pb3 (PO4)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…S2). These effects are consistent with prior studies in a number of organisms and cell types demonstrating the impact of Pb 2ϩ on various aspects of metal (37-42), phosphate (43,44), and sulfur homeostasis (45)(46)(47).…”
Section: Stress-induced Heme Signalingsupporting
confidence: 91%
“…S2). These effects are consistent with prior studies in a number of organisms and cell types demonstrating the impact of Pb 2ϩ on various aspects of metal (37-42), phosphate (43,44), and sulfur homeostasis (45)(46)(47).…”
Section: Stress-induced Heme Signalingsupporting
confidence: 91%
“…A white precipitate was evident upon addition of P043or C032to the Pb-amended medium. The toxicity of Pb to growth of Chlamydomonas reinhardtii was also reduced by the incorporation of P043into the medium (35), and the toxicity of Pb to Tetrahymena pyriformis was greater in soft (20 mg of CaCO3 per liter) than in hard (400 mg of CaCO3 per liter) water (11), possibly due to the formation of greater quantities of PbCO3 in the hard water. Similarly, the sparingly soluble Pb salts, PbO, PbS, and PbCO3.Pb(OH)2, were not toxic to A. niger, whereas equivalent concentrations of free Pb2+ were highly toxic (46).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of 102 M succinic acid to the medium also reduced the inhibitory or lethal effect of 200 ,tg of Pb per ml to R. solani, F. solani, A. giganteus, and C. echinulata (Table 6), probably as a result of the chelation of Pb by the dicarboxylic acid. Chelated forms of Pb were also less toxic to growth of A. niger (46) and C. reinhardtii (35) and were less readily taken up by Phaeodactylum tricornutum (34) than was free Pb.…”
Section: Resultsmentioning
confidence: 99%
“…Since the experiments were done with P-repleted cultures, it was not expected that the algae would suffer P-limitation during exposure, thus, the results support the alternative hypothesis that P–Cu interaction in the media leads to a reduction in Cu bioavailability. It has been shown that phosphate precipitates with other metals and that this leads to decreased metal availability (Schulze and Brand 1978 ; Nalewajko and Paul 1985 ). However, this argument is difficult to apply to natural systems since a copper phosphate precipitate is thermodynamically unlikely to occur in natural waters, because of the presence of competing ligands.…”
Section: Discussionmentioning
confidence: 99%